ANALYSES OF BANJARMASIN’S KM. 6 TERMINAL PERFORMANCE BY MEANS OF IMPORTANCE-PERFORMANCE ANALYSIS METHOD - Idrus Idrus (Lambung Mangkurat University Press, 2015)
The Banjarmasin’s Km.6 Terminal is an important component in the city’s transportation system, which is an enter-exit point of both passengers and cargos from the system. The terminal is not only the main functional component of the system, but also an infrastructure that requires a lot of resources and a place where traffic jam commonly occurs. Hence, a research needs to be conducted to evaluate the performance of Banjarmasin’s Km.6 Terminal by means of Importance-Performance Analysis based on the perception of both the uses and the providers of the service.The method being used here is the Importance-Performance Analysis (IPA), by measuring the performance of Banjarmasin’s Km.6 Terminal, based on the interest level assessment of the service providers, and performance assessment from the service users.The research shows high level of interest category in Banjarmasin’s Km. 6 Terminal’s performance according to the service providers, and low category for the assessment from the service users. From the assessment’s indicators, it is found that the terminal’s technical requirements, the terminal’s operational requirements, the terminal’s officers’ availability, and the terminal’s vehicle capacity are the indicators that have not yet met the requirement and therefore, must be prioritized to be improved.